O-207 Which infertile patients mostly deserve to have a sperm DNA fragmentation index done? Findings from a cross-sectional study. (6th August 2021) - Pozzi, E; Boeri, L; Candela, L; Cignoli, D; Colandrea, G; Raffo, M; Cazzaniga, W; Schifano, N; Capogrosso, P; Ventimiglia, E; Abbate, C; Montorsi, F; et al.
Abstract: Study question: Current scientific guidelines do not clearly suggest which patients would benefit the most from a sperm DNA fragmentation (SDF) test. Summary answer: We aimed to investigate potential predictive factors for altered SDF in a homogenous cohort of white-European men presenting for primary couple's infertility. What is known already: High SDF has been associated with reduced fertilization rates, reduced chances of natural conception and an increased risk of early pregnancy loss. Study design, size, duration: Data from 478 consecutive men with normal or altered SDF were analysed. Infertility was defined according to the WHO criteria. Semen analysis, SDF (according to SCSA) and serum hormones were measured in every patient. Health significant comorbidities were scored with the Charlson Comorbidity Index (CCI). Altered SDF was considered with a threshold of > 30%. Participants/materials, setting, methods: Descriptive statistics compared the overall characteristics of patients with normal SDF and altered SDF. Logistic regression analysis tested potential predictors of altered SDF. ROC curve was used to test the accuracy of the model in predicting SDF alteration Main results and the role of chance: Of 478 patients, 253 (57.7%) had altered SDF. Median (IQR) age and BMI of the whole cohort were 38 (35-42) years and 25.1 (23.3-27.1) kg/m 2 respectively. Patients with altered SDF were older (median (IQR) age: 39 (36-43) vs. 37 (34-38) years, p < 0.0001), had lower sperm concentration (5 (1.1–18) vs. 17 x10 6 /mL (6–38.8), p < 0.0001), testicular volume (15.1 (12 –20) vs. 16.8 (12 – 25) Prader, p = 0.0005), and total motile sperm count (TMSC) (1.8 (0.21–10.71) vs. 11.8x10 6 (2–37.26), p < 0.0001). Conversely, men with altered SDF had higher FSH (6.1 (3.85–9.7) vs. 4.8 (3.85 – 7.9) mIU/mL, p < 0.0001) and prolactin levels (9.8 (7.43–14.04) vs. 8.3 (6.6–11.3) pg/mL, p = 0.0004) than those with normal SDF. At multivariable logistic regression analysis, patients' age >35 years (OR: 2.45, p = 0.0009), FSH > 8.0 mIU/mL (OR: 2.23, p < 0.0001) and lower TMSC (OR: 2.04, p = 0.002) were identified as indipendent predictors of altered SDF, after adjusting for testicular volume and CCI≥1. ROC curve (Figure 1) revealed that the model has a good predictive ability to identify patients with SDF alteration (AUC: 0.72, 95%CI: 0.67 - 0.77). Limitations, reasons for caution: It is a retrospective analysis at a single, tertiary-referral academic centre, thus raising the possibility of selection biases. In spite of this, all patients have been consistently analysed over time with a rigorous follow-up, thus limiting potential heterogeneity in terms of data reporting Wider implications of the findings: Primary infertile men older than 35 years, with high serum FSH and low TMSC at baseline are the ones who mostly deserve a SDF test over their diagnostic work-up and that would potentially benefit the most of certain treatments to improve SDF value, thus increasing chances of conceiving. Trial registration number: Not applicable